Femtosecond Laser-Induced Formation of Gold-Rich Nanoalloys from the Aqueous Mixture of Gold-Silver Ions. (8th November 2010) - Herbani, Yuliati; Nakamura, Takahiro; Sato, Shunichi
Abstract : The synthesis of gold-silver (AuAg) nanoalloys of various compositions has been performed by direct irradiation of highly intense femtosecond laser pulse in the presence of polyvinylpyrrolidone (PVP). The mixture of Au and Ag ions of low concentration was simply introduced into a glass vial and subjected to femtosecond laser pulses for several minutes. The AuAg nanoalloys of 2-3 nm with reasonably narrow size distribution were formed, and the position of the surface plasmon resonance (SPR) increased monotonically with an increase in the gold molar fraction in the ion solutions. The high resolution transmission electron microscope (HRTEM) images exhibited the absence of core-shell structures, and the energy dispersive X-ray spectroscopy (EDX) analysis confirmed that the particles were Au-rich alloys even for the samples with large fraction of Ag + ions fed in the solution mixture. The formation mechanism of the alloy nanoparticles in the high intensity optical field was also discussed.